Taxonomic study of Sinopoda spiders from China (Araneae: Sparassidae) - Zhong, Yang; Jäger, Peter; Chen, Jian; Liu, Jie (Zootaxa, 2019)
The spider genus Sinopoda Jäger, 1999 in China is studied. Seventeen new species are described: S. abstrusa sp. nov. (♂♀, Xizang), S. aequalis sp. nov. (♂♀, Henan), S. apiculiformis sp. nov. (♂♀, Hunan), S. brevis sp. nov. (♂♀, Liaoning), S. changde sp. nov. (♂♀, Hunan, Shaanxi), S. columnaris sp. nov. (♀, Guizhou), S. curva sp. nov. (♂, Guangxi), S. dehiscens sp. nov. (♀, Hunan), S. erromena sp. nov. (♀, Hunan), S. improcera sp. nov. (♂♀, Yunnan), S. lata sp. nov. (♀, Yunnan), S. luyui sp. nov. (♂♀, Sichuan, Gansu), S. ovata sp. nov. (♂♀, Chongqing), S. pyramidalis sp. nov. (♂♀, Sichuan), S. tumefacta sp. nov. (♂♀, Yunnan), S. yaanensis sp. nov. (♂♀, Sichuan, Yunnan), S. yanlingensis sp. nov. (♂♀, Hunan). Five known species are redescribed or diagnosed and differentiated from related species: the males of S. liui Zhong, Cao & Liu, 2017 and S. longshan Yin, Peng, Yan & Bao, 2000 and the female of S. pengi Song & Zhu, 1999 are reported for the first time; the female of S. longiducta Zhang, Zhang & Zhang, 2015 is considered mismatched and transferred to S. yaanensis sp. nov.; photographs and new records are provided for S. globosa Zhang, Zhang & Zhang, 2015.